TOTAL ANTIOKSIDAN DARI BEBERAPA JENIS SAYURAN TINUTUAN YANG DITANAM DI DAERAH BERBEDA KETINGGIAN - Momuat, Lidya; Fatimah, Feti; Wehantouw, Frenly; Mamondol, Oktavianus (Sam Ratulangi University, 2011)
ABSTRACTMomuat et al., 2011. Total antioxidant of some Tinutuan vegetables planted in different altitude places.A research was done to to study the effect of altitude on total antioxidant some tinutuan vegetables. Totalantioxidant of some vegetables was evaluated using ferric reducing antioxidant plasma method. The resultsshow that vegetables treat by heating possessed high antioxidant activity. Total antioxidant of gedi, spinach,kangkung and kemangi from Tomohon were 0.02, 1.37, 0.06 and 0.08, respectively. Total antioxidant of gedi,spinach, kangkung and kemangi from Manado were 0.36, 1.84, 0.30 and 0.58, respectively. High totalantioxidant activity of vegetables from Manado caused by Manado land contain more minerals to support plantgrowth and metabolism.Keywords : altitude, vegetables, tinutuan, total antioxidant